Students' Perception on Their Motivation in Learning English (The Analysis Students' Motivation Based on Maslow's Concept) - Agus Udong Rapiudin (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2019)
The present study aims at analyzing the students' perception toward their motivational need in learning English. The need to learn English is important to be identified so that the education stakeholders catering the students' learning program can possibly figure out the relatively suitable service given to the students. The present study used mixed method. Two instruments were administered to elicit the students' perception on their motivational need as well as finding the determinants /factors which might have affected their motivation. The research findings indicated that the students mostly believed in the importance of learning English. However, at the same time they also indicated that their learning English was a mere instrumental and not for the sake of establishing relationship or living in an English speaking communities. They also considered that while English is important to help them realize their dream, they considered that other skills are also important for actualizing their dream.